Distribution of heavy metals and polycyclic aromatic hydrocarbons in holm oak plant–soil system evaluated along urbanization gradients. (September 2015) - De Nicola, Flavia; Baldantoni, Daniela; Sessa, Ludovica; Monaci, Fabrizio; Bargagli, Roberto; Alfani, Anna
Highlights: Concentration ratios allow to evaluate the fate of pollutants in plant–soil systems. HMs and PAHs are subjected to a different fate in leaves and in soil. HM Q. ilex leaf concentrations mainly depend on root uptake and translocation. PAH Q. ilex leaf concentrations mainly depend on atmospheric depositions. High molecular weight PAHs are preferentially deposited on soil. Abstract: Heavy metals (HMs) and polycyclic aromatic hydrocarbons (PAHs) were analysed in topsoil and in Quercus ilex L. leaves from holm oak woodlands located along urbanization gradients (urban, periurban and extraurban sites) in two Italian regions (Campania and Tuscany). In each sampling site, the metal bioavailability factors (MBFs) and the pollutant bioaccumulation factors (BAFs) were calculated to estimate the fraction of each total metal concentration in soil potentially available to root uptake and to know the fate of both HMs and PAHs in the plant–soil system. In general, the results indicated a low atmospheric deposition of pollutants and, in some cases, leaves and soils accumulated higher HM and PAH concentrations in the most urbanized areas. Correlation analyses showed that in each sampling site topsoil and leaves were exposed to the same atmospheric inputs of HMs and PAHs, although to a different extent. Notwithstanding the MBFs and BAFs differed between the two regions for the most HMs, they did not show a clear pattern in relation to the urbanization gradient. However, some information could be deduced by these ratios: the high BAF calculated for Mn shows that the foliar uptake plays an important role in accumulation of this metal. Moreover, for PAHs the different values of BAFs among low and high molecular weight compounds suggest their different fate, the first accumulated in leaves by stomata and the latter preferentially deposited on topsoil.